VIth World Congress on Science and Football, Book of Abstracts, January 16-20, 2007, Antalya, Turkey - Poster Presentations - Physiological Testing of Football Players (Journal of Sports Science & Medicine, 2007)
Summaries on the following topics: P-001 Yo-Yo intermittent recovery performance test, body composition and biochemistry markers in young soccer players P-002 Oxygen uptake during soccer P-003 Aerobic fitness in futsal players of different competitive level: a preliminary study P-004 Technical performance during short term soccer specific exercise P-005 Reliability of a repeated sprint ability test during simulated team-sport running activity on a non-motorised treadmill P-006 Comparison of anaerobic tests in young soccer players P-007 Anaerobic power of junior elite soccer players: A new performance P-008 Validity of aerobic field tests in young soccer players P-009 Effects on training status and health profile of prolonged participation in recreational football: Heart rate response to recreational football training and match-play P-010 Physiological effects of playing futsal in professional futsal players P-011 Fitness profile of under-15 Brazilian soccer players by field position P-012 Running velocities and heart rate responses to fixed blood lactate concentration in different divisions of professional soccer players P-013 Left ventricular hypertrophy by electrocardiographic point scoring criteria in professional soccer players and sedenters P-014 Yo-Yo intermittent recovery test level 2 in evaluation of physical performance in different groups of athletes P-015 Physiological responses of young soccer players to fixed lactate concentrations in playing positions P-016 Fitness demands of soccer players P-017 The comparison of sprint performances of left and right legged soccer players P-018 Heart rate and perceptual responses to 2x2 and 3x3 small-sided youth soccer games P-019 Physical preparedness of soccer players in third and first Russian football leagues P-021 Ability to repeat sprint and maximal aerobic power in young soccer players P-022 The effects of a 10 week plyometric training intervention on 10 m sprint and vertical jump performance in elite junior professional soccer players P-023 Impact of pre-cooling on soccer-specific exercise (SSE) performed in heat P-024 Comparison of a new soccer-specific aerobic fitness test to other field and laboratory tests: Preliminary data P-025 Playing standard and position-specific differences in performance of a soccer-specific aerobic fitness test (SAFT): Preliminary data P-026 Physiological and health variables of sports trainers P-027 Relationships of body composition, anaerobic performance and isokinetic knee strength in American football players P-028 Aerobic and anaerobic fitness indicators in under 20 and elite Qatari soccer players P-029 Pre-season aerobic performance of elite Japanese soccer players P-030 Physiological responses to submaximal and maximal exercise intensities: Field versus laboratory P-031 Validity of a group intermittent-high-intensity test for repeated sprint ability P-032 Assessing aerobic and anaerobic power from a 90-s all-out isokinetic test versus the Wingate test in young female soccer players P-033 Season variation in repeated sprint ability of futsal players P-034 Quantifying energy expenditure of dribbling a soccer ball in a field test P-035 Explosive strength performance of under-20 soccer players in different field positions P-036 Effects of intermittent hypoxic exposure on haematological and performance in soccer players P-037 Effect of knee muscle strength on level of professionalism in soccer players P-038 Anthropometric parameters and manifestations of strength and speed in soccer players in ages of formation P-039 Changes in speed, explosive strength and anaerobic power after application of two different training methods in soccer players P-040 Assessment of anthropometric characteristics and sprint velocity in soccer players from 5 different age groups